Asbabun Nuzul Ayat-Ayat Tauhid sebagai Pembelajaran Penelusuran Formula dalam Analisis Biaya-Volume-Laba - Rusdin, Muhammad; Hawariah, Hawariah; Fadhlan Akbar; Irwan Fitri Aco; Asri Asri (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research aims to find out some of the asbabun nuzul verses of monotheism as a lesson for exploring formulas in cost-volume-profit analysis, including the break-even point formula. This interdisciplinary research is library research using qualitative descriptive analysis methods and quantitative descriptive methods. The results of this research show: 1) Most of the verses from the Qur'an are ibtidai verses, namely verses without asbabun nuzul. A small portion of the verses of the Qur'an are sababi verses or verses with asbabun nuzul because they are for: answering questions, rebuking violations, rejecting the world's offers and so on. Meanwhile, the existence of formulas in cost-volume-profit analysis is due to knowing the sales limit that brings profit/loss. These formulas are caused or started from the break-even formula that was developed. 2) A small portion of the verses from the Qur'an are monotheism verses which mean the only God who must be worshipped, the only Creator, the only Most Gracious, the only Most Merciful and other attributes. Meanwhile, in the break-even formula and other formulas in cost-volume-profit analysis, the only number is meaningful or caused by the selling price divided by the selling price.